Wisconsin Department of Transportation Highway Pavement Ride Analysis: The Effects of Specification Changes on Newly- Constructed Pavement - Reichman, Stefanie (My University, 2018)
Abstract Smoothness specifications are implemented by all State Highway Agencies (SHA) to promote overall roadway quality and optimize rider comfort. There are several key benefits of improved roadway initial smoothness, the first of which is increased user comfort, fuel efficiency, and increased roadway lifetime. Wisconsin Department of Transportation (WisDOT) ride specification utilizes pay adjustments (incentives and disincentives) to achieve those objectives. This study investigates the efficiency of these specifications and their changes over the last eleven years (2007-2017), which includes five different specifications. The focus of this study is the effect of specifications on newly constructed roadways over time and the incentive payments made for all types of asphalt and concrete pavement. Though there are a broad range of studies which have evaluated ride smoothness, there is a gap in studies which aggregate and capture specification changes and their effects on roadway smoothness. In this study, the investigation found that the specification changes have made an impact only on specific asphalt and concrete types. Specifically, both mainline pavement types (HMA I and PCC II) have exhibited smoother roads over the study period. As such, it is the resulting conclusion that specifications should be more closely tailored to the different needs of each specific pavement type. Notably, concrete and asphalt segments were found to be significantly different from each other, yet the specifications group the different pavement types together when the data does not support this grouping. The study also proposes different potential optimization cases that WisDOT may pursue to improve current specification pay adjustments, which would have cost savings to WisDOT. Additionally, this study analyzes the effects of specifications on localized roughness, which are segments of increased roughness, above a threshold. The current specification, with threshold of 200 inches/mile, has shown significant improvement over the past thresholds of 150 and 175 inches/mile, in terms of average roadway smoothness. The results from the concrete localized roughness determined a potential for improved education so that segments are not mislabeled and misanalysed. The specification changes did not impact concrete as significantly as it did for asphalt. Though the thresholds are the same. Lastly, the study analyzed project segments built under a warranty type specification. The warranty analysis did show that warranty projects had a lower initial smoothness as compared to non-warranty segments. The warranty program was suspended in 2012, due to long term quality concerns.
Keywords: WisDOT